2008
DOI: 10.4315/0362-028x-71.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Quantification of Tyrosine Decarboxylase Gene (tdc) and Its Expression in Gram-Positive Bacteria Associated with Fermented Foods Using PCR-Based Methods

Abstract: In this study, PCR-based procedures were developed to detect the occurrence and quantify the expression of the tyrosine decarboxylase gene (tdc) in gram-positive bacteria associated with fermented foods. Consensus primers were used in conventional and reverse transcription PCR to analyze a collection of 87 pure cultures of lactic acid bacteria and staphylococci. All enterococci, Staphylococcus epidermidis, Lactobacillus brevis, Lactobacillus curvatus, and Lactobacillus fermentum strains and 1 of 10 Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 28 publications
0
50
0
2
Order By: Relevance
“…RNA extraction and reverse transcription-PCR procedures were performed as previously described (20). At the tetracycline concentration tested, tet(S) was always expressed, while expression of the genes tet(M) and tet(L) was found only in a few strains (Table 3).…”
Section: Tet(l) Tet(m) Tet(o) Tet(s) and Tet(w)]mentioning
confidence: 99%
“…RNA extraction and reverse transcription-PCR procedures were performed as previously described (20). At the tetracycline concentration tested, tet(S) was always expressed, while expression of the genes tet(M) and tet(L) was found only in a few strains (Table 3).…”
Section: Tet(l) Tet(m) Tet(o) Tet(s) and Tet(w)]mentioning
confidence: 99%
“…Tyramine formation is the result of bacterial decarboxylation of tyrosine that is carried out by several microorganisms, including strains of lactic acid bacteria (LAB) belonging to different genera and species (7,23). Among LAB, Streptococcus thermophilus is of major importance for the dairy industry, where it is commonly used in starter cultures for the manufacture of yogurt, fermented milks, and many varieties of cheese.…”
mentioning
confidence: 99%
“…3, as follows: 1 volume of 26.8 mM EDTA, pH 12.0 (18), was added to 4 ml of the milk culture, and the mixture was centrifuged and washed twice with sterile water. The extraction was carried out as described by Torriani et al (23). RNA integrity, concentration, and purity were checked by electrophoresis on 2% (wt/vol) agarose gel and by measurement of the OD 260 /OD 280 ratio.…”
mentioning
confidence: 99%
“…Recently, histidine decarboxylase genes have been characterized in S. capitis (16) and S. epidermidis (K. Yokoi and K. Kodaira, unpublished data; GenBank accession no. AB378754), while a fragment of a putative tyrosine decarboxylase gene was described in an S. epidermidis strain (46). Genome sequencing has demonstrated that putrescine production by ornithine decarboxylation is a trait that is abundantly found in the Gram-negative Gammaproteobacteria but rarely in Gram-positive bacteria.…”
mentioning
confidence: 99%